Cardiovascular involvement in COVID-19 - Germán, Valenzuela-Rodríguez (2020)
Cardiovascular compromise among COVID-19 patients, especially in the subpopulation with cardiovascular risk factors, is associated with severity of disease and a higher mortality in some case-series.The most clearly described pathophysiological mechanisms are direct myocardial injury and the process associated with systemic inflammation. Cardiovascular manifestations are diverse and include myocardial injury, myocarditis, cardiomyopathies, heart failure, acute coronary syndromes, arrhythmias, thromboembolic events. Moreover, we must consider the adverse effects of medications used to treat the viral infection.